ADS024, a single-strain live biotherapeutic product of Bacillus velezensis alleviates dextran sulfate-mediated colitis in mice, protects human colonic epithelial cells against apoptosis, and maintains epithelial barrier function - Irwin, Sophie; Chupina Estrada, Andrea; Nelson, Becca; Bullock, Ashlen; Limketkai, Berkeley; Ho, Wendy; Acton, Susan; Chesnel, Laurent; Koon, Hon Wai (Frontiers in Microbiology, 2024)
Epithelial cell apoptosis and compromised gut barrier function are features of inflammatory bowel disease. ADS024 is a single-strain live biotherapeutic product (LBP) of Bacillus velezensis under development for treating ulcerative colitis (UC). The cytoprotective effects of the sterile filtrate of ADS024’s secreted products on UC patient-derived colonic tissues, human primary colonic epithelial cells (HPEC), and human colonic epithelial T84 cells were evaluated. ADS024 filtrate significantly inhibited apoptosis and inflammation with reduced Bcl-2 Associated X-protein (BAX) and tumor necrosis factor (TNF) mRNA expression in fresh colonic explants from UC patients. Exposure to UC patient-derived serum exosomes (UCSE) induced apoptosis with increased cleaved caspase 3 protein expression in HPECs. ADS024 filtrate diminished the UCSE-mediated apoptosis by inhibiting cleaved caspase 3. TNFα and interferon-gamma (IFNγ) damaged epithelial barrier integrity with reduced transepithelial electrical resistance (TEER). ADS024 filtrate partially attenuated the TEER reduction and restored tight junction protein 1 (TJP1) expression. Oral live ADS024 treatment reduced weight loss, disease activity, colonic mucosal injury, and colonic expression of interleukin 6 (IL-6) and TNFα in dextran sodium sulfate (DSS)-treated mice with colitis. Thus, ADS024 may protect the colonic epithelial barrier in UC via anti-inflammatory, anti-apoptotic, and tight-junction protection mechanisms.